Evaluating financial literacy impact on business performance, the Zimbabwean SMEs experience - Nyarusanga, Lazarus (Midlands State University, 2019)
The research study was an evaluation of financial literacy’s impact on business performance, the Zimbabwean SMEs experience. The study was based on a survey of SME businesses across Zimbabwe who were reached for responses through structured questionnaires and interviews. The researcher used both primary and secondary data sources from a sample of 300 respondents. The sample was chosen from various value chain players across industries dominating the Zimbabwean SME landscape. The data collected were analysed using the SPSS Statistics Version 21 application to conduct the reliability tests (Cronbach Alpha), correlation and regression analysis which produced descriptive statistics such as frequencies, simple percentages out of which the comparatives between the variables of the model were tested using multiple linear regression analysis. Testing the firsts to third hypotheses, at 5 % level of significance, the p-values (0.0005) were all lower than the significance level and concluded that at the 95% significant level financial literacy impacts business performance of SMEs to a greater extent. For all the hypotheses tested the null hypothesis was accepted and the alternative hypotheses rejected. After testing the second hypothesis, it was concluded that financial literacy is highly and positively correlated with business performance. The probability value of the regression analysis was used to test the third hypothesis at the same level of significance and since the p-value was also lower than the significance level, it was concluded that there are other factors that impact on business performance such as the internal and external factors to business. Overally it was therefore concluded that financial literacy level impacts highly on business performance of SMEs and among key recommendations is that governments prioritise literacy training of SMEs as they are critical to economic growth. The study also recommended that future studies look at other aspects such as the impact that external factors have on SME business performance